A novel missense mutation in the amino-terminal domain of the human androgen receptor gene in a family with partial androgen insensitivity syndrome causes reduced efficiency of protein translation. - Choong, C S (1996)
The role of the androgen receptor (AR) in male sexual differentiation is revealed in part by the analysis of naturally occurring mutations in families with androgen insensitivity syndrome (AIS). We have investigated a family with partial AIS affecting three generations and have identified a G to A substitution in the AR gene at the fourth position 3' from the A of the ATG initiation codon changing the second amino acid residue from glutamic acid to lysine (EK2). Transient expression of the mutant EK2-pCMVhAR expression vector in COS cells revealed decreased translation with a 20-50% reduction in mutant protein relative to wild type AR by immunoblot analysis. The rate of dissociation of [3H]methyltrienolone from the EK2 mutant (half-time [t1/2] = 1.7 +/- 0.08 SE h) was increased compared with wild type AR (t1/2 = 2.4 +/- 0.11 h). Cotransfection studies using an androgen responsive luciferase reporter vector demonstrated a 50% reduction in transcriptional activation by EK2. These functional alterations are consistent with the partial AIS phenotype in affected males, corroborate the AR amino-terminal domain effect on kinetics of androgen binding, and provide physiological evidence for earlier translation experiments identifying the nucleotide sequence for optimal translation initiation.